THE IMPACT OF ORGANIC CERTIFICATION ON THE COMPETITIVENESS OF COMPANIES EXPORTING MEDICINAL PLANTS - Boiko, Dmytro (European Journal of Interdisciplinary Issues, 2025)
The relevance of the study is due to the growing demands of the international market for safety, transparency and traceability of plant products, which makes it impossible for Ukrainian exporters of medicinal raw materials to compete effectively without internationally recognized organic certification. At the same time, the sector still faces the problems of regulatory non-compliance, high costs and limited availability of certification procedures, which hinder the integration of Ukrainian producers into premium sales channels. The article is aimed at substantiating the impact of organic certification on the formation of competitiveness of enterprises exporting medicinal plants, taking into account economic, institutional and technological factors in the context of the current global situation. Research methodology. The methodological basis is the content analysis of international standards (EU Organic, USDA NOP, Bio Suisse, Naturland), statistical analysis of export dynamics in 2006–2023, comparative analysis of price indicators of certified and non-certified products, as well as generalization of applied cases of Ukrainian exporters and data from official reports of TRACES, Organic Standard, FiBL. It was found that the certificate increases the selling price of products by 15–25%, reduces the share of cargo returns to 0.5%, and provides access to new sales channels and tenders from leading European traders. A direct correlation between the certification status of the manufacturer and the stability of export contracts is revealed. The importance of institutional support and digital infrastructure (TRACES, DUNS) for export scaling is substantiated. Scientific novelty. For the first time, the quantitative and qualitative effects of organic certification are summarized in the context of medicinal plant exports from Ukraine, barriers to access to organic markets are structured, and practical mechanisms for strengthening the market position of small and medium-sized producers through certification instruments are outlined. It is proved that certification is a key tool for strengthening the international competitiveness of Ukrainian exporters of medicinal plants. Successful implementation of certification strategies requires the involvement of state support, institutional support, development of cooperation and raising awareness of producers about the benefits of certified exports. Prospects for further research. An in-depth study of the mechanisms of clustering organic production, the long-term socioeconomic effects of involving households in certified medicinal crops, as well as an assessment of the possibilities of implementing digital solutions for traceability and certification monitoring seems advisable.